Religio-cultural heritage of libation, memory and Obang cultural history, Northwest Cameroon - Esoh, Felix K. (HTS teologiese studies, 2020)
This article argues that libation, often associated with the ancestors, artefacts, images and pre-Christian religious devotions, constitutes sources for articulating authentic African cultural history of Obang community in the Northwest Region of Cameroon. It highlights that among traditional memory carriers, the ritual of libation remains trust worthy and pervasive, even among communities challenged by globalisation and colonising effects of Christianity. The article demonstrates the immense potentials of libation as an epitome and stabiliser of cultural memory, and a maxim in cultural resilience in contemporary Africa. Thus, the article calls for revisiting this ancient ritual to expose its potentials as a veritable memory repertoire in cultural–historical studies, especially at a time when social change and modernism continue to challenge the memories of traditional societies.